Eksplorasi kesulitan siswa SMP dalam menjawab soal kemampuan pemecahan masalah matematis pada materi fungsi kuadrat - Neng Lia Puji Astuti; Asep Ikin Sugandi; Citra Megiana Pertiwi (IKIP Siliwangi, 2023)
The importance of mathematical problem-solving abilities for students is that they enable students to overcome various difficulties encountered in order to achieve a goal that is expected in terms of mathematics and everyday life. The research aimed at exploring the causes of difficulties in students' mathematical problem-solving abilities when solving story questions on quadratic functions. Data collection in the research carried out was carried out by giving four items about mathematical problem solving abilities in the quadratic function material. The subject of this research was conducted on 20 grade IX junior high school students in the city of Cimahi. The data analysis technique in this study was descriptive qualitative with the aim of providing a description of students' mathematical problem solving abilities when solving problems on quadratic function material. Based on the research conducted, it was found that students who were able to understand problems as big as they were in medium criteria, students who were able to plan a settlement were in medium criteria, students who were able to make solutions were in medium criteria, and students who were able to check back were in low criteria.